Analisis Penurunan Tingkat Kecacatan untuk Produk Paper Core di PT. X - Abner Dikman Pinasthika; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2023)
PT. X is a company engaged in packaging production, specifically paper core, which was established in 2001. The production system of PT. X operates on a made-to-order principle, manufacturing products according to customer orders and specifications. The success of meeting customer needs is crucial for business progress and sustainability, making quality management increasingly important in business competition. It can enhance customer satisfaction, maintain company reputation, reduce production costs, and improve profitability. Production data from March to April 2023 revealed a 20% defect rate in the grinding, coating, and polishing processes for paper core production, with